Correction to: Hypoxemia in the ICU: prevalence, treatment, and outcome - SRLF Trial Group (Annals of Intensive Care, 2019)
Following publication of the original article [1], we have been notified that only the 11 members of the writing committee are listed as the collaborators of the SRLF Trial group